Evaluation of the Use of Antihypertensive Agents in Ischemic Stroke Patients Hospitalized in West Nusa Tenggara Hospital, Indonesia - Baiq Leny Nopitasari; Cyntiya Rahmawati; Anna Pradiningsih; Baiq Nurbaety (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2021)
Antihypertensive agents are one of the drugs recommended on ischemic stroke patients as a secondary therapy for prevention of occurrence repeated stroke and reduce the risk of brain edema. If the management of hypertension is incorrect on ischemic stroke patient can worsen the patient's condition and affect mortality. The use of antihypertensive drugs must be evaluated accordingly with rational use of drugs. This study aims to examine the accuracy of the use of antihypertensive drugs in ischemic stroke patients which includes right indication, right patient, right medicine, right dose and right frequency. This research is a cross sectional descriptive study using medical record data of 19 ischemic stroke patients. The inclusion criteria of the study were all ischemic stroke hospitalization patients and receiving antihypertensive drugs therapy. The evaluation of accuracy was done descriptively by comparing research data to the literature which includes JNC VII & VIII, PERDOSSI 2011, PIONAS 2015, FORNAS and Revised RSUDP Formulary 6th. The results showed the accuracy of use antihypertensive agents is 100% that is 100% precise indication; 100% right patient; 100% right dose; and 95% right frequency. The type of inaccuracy encountered is frequency imprecision drug administration, therefore the role of a pharmacist in hospital are needed as part of efforts to improve the accuracy of the use of drugs in ischemic stroke patients.